PENGARUH ANALISIS STRATEGI DIGITAL MARKETING DAN KEPERCAYAAN MEREK DALAM MEMBENTUK KEPUTUSAN PEMBELIAN: STUDI KASUS DI TOKO RODEO RAJANYA KANDANG - Aldio Farri Reza; Defrizal (Berajah Journal, 2026)
This study aimed to analyze the influence of digital marketing strategies and brand trust on purchasing decisions at the Rodeo Rajanya Kandang store. This research employed a quantitative approach, utilizing SPSS software as a data analysis tool. To assess data quality, validity and reliability tests were conducted, followed by a series of classical assumption tests: normality, multicollinearity, and heteroscedasticity. Hypothesis testing was conducted using a t-test, followed by a coefficient of determination analysis. This study involved 100 respondents, with the entire population being sampled using a saturated sampling technique. Data processing revealed that digital marketing strategies and brand trust have a positive and significant influence on purchasing decisions at the Rodeo Rajanya Kandang store.